The value of the neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio as complementary diagnostic tools in the diagnosis of rheumatoid arthritis: A multicenter retrospective study. Issue 1 (19th September 2020) - Jin, Zihan; Cai, Gaojun; Zhang, Ping; Li, Xiaohong; Yao, Shuang; Zhuang, Lin; Ren, Min; Wang, Qiang; Yu, Xiaolong
Abstract: Background: The neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) have drawn attention in recent years as novel non‐specific inflammatory markers; however, only a few studies have been conducted to investigate their value in RA. Objective: To investigate the value of the neutrophil‐to‐lymphocyte ratio (NLR) and the platelet‐to‐lymphocyte ratio (PLR) as complementary diagnostic tools in rheumatoid arthritis (RA). Method: This study included 1009 patients with RA, 170 patients with other rheumatic diseases, and 245 healthy individuals from four medical centers. The patients' general data, including complete blood count, C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR), and rheumatoid factor (RF), were retrospectively analyzed, and the NLR and PLR were calculated. Potential effective indicators were screened by logistic regression analysis, and a receiver operating characteristic (ROC) curve was plotted to evaluate their diagnostic value for RA. Results: (a) The NLR and PLR were significantly higher in the RA group than in the non‐RA group and the control group ( P  < .05). (b) Spearman's Rho showed that the NLR was positively correlated with the PLR ( r  = .584, P  < .05), RF ( r  = .167, P  < .01), and CRP ( r  = .280, P  < .01) but was not significantly correlated with ESR ( r  = .100, P  > .05). The PLR was positively correlated with RF ( r  = .139, P  < .01), CRP ( r  = .297, P  < .01), and ESR ( r  = .262, P  < .05). (c) Logistic analysis showed that RF, CRP, ESR, and the NLR had diagnostic value for RA. (d) For the NLR, the area under the curve (AUC) of the ROC curve was 0.831; at the cutoff value of 2.13, the diagnostic sensitivity, specificity, accuracy, and Youden index were 76.7%, 75.9%, 76.4%, and 0.5424, respectively. Conclusion: The NLR was less effective than CRP and RF but was superior to ESR in the diagnosis of RA. The NLR can thus be used as a complementary diagnostic indicator in the diagnosis of RA. Abstract : The ROC curve of the diagnostic value of the NLR for RA. At the cutoff value of 2.13 and an AUC of 0.831, the diagnostic sensitivity, specificity, and accuracy were 76.7%, 75.9%, and 76.4%, respectively, which were lower than the corresponding values for RF and CRP but higher than those for ESR. RF: rheumatoid factor; CRP: C‐reactive protein; ESR: erythrocyte sedimentation rate; NLR: neutrophil‐to‐lymphocyte ratio; Pre‐1: predicted probability‐1.